Water-based drilling fluid high-temperature-resistant plugging agent and preparation method thereof
By using composite technology of inlaid particles, micro-expanding agents, structural enhancers and low-permeability rigid particles in the plugging agent, the problem of poor leakage plugging performance of existing plugging agents under high temperature conditions is solved, and the efficient sealing effect of water-based drilling fluid anti-high temperature plugging agent is achieved.
Patent Information
- Application Number
- CN202311320602.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-15
AI Technical Summary
The existing leak plugging agent has poor leak plugging performance under high temperature conditions and cannot effectively seal the pores and cracks in high-temperature formations, making it difficult to solve the well leakage problem.
Water-based drilling fluid anti-high temperature leak plugging agent is used. This agent is composed of inlaid particles, micro-expanding agent, structural enhancer and low-permeability rigid particles. Through the combination of different particle sizes and materials, a wide particle size distribution is formed to improve the leak plugging effect.
After aging at 180°C, the performance of water-based drilling fluid anti-high temperature leak plugging agent is stable, which can effectively form sealing and blockage, significantly improve the resistance to high temperature, and overcome the defect of the single grading of conventional micro-nano leakage plugging materials and cannot resist high temperatures.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plugging agents, in particular to a water-based drilling fluid high-temperature resistant plugging agent and a preparation method thereof. Background Art
[0002] In view of the well leakage problem caused by the mid-to-late stage of oil and gas field development, effective drilling leakage prevention and plugging technologies are needed to solve it. At present, the commonly used plugging materials are drilling plugging agents and ultrafine calcium plugging agents. However, there are some problems in the implementation of traditional plugging methods, resulting in a low plugging success rate. First, the opening size of the micro-cracks in the leaking layer is large, while the particle size of the plugging material is small, especially the hard particle material is more difficult to form an effective bridge plug in the crack; second, when the crack opening size is small, large particle materials are prone to form a sealing phenomenon, which hinders the entry of smaller particle materials, resulting in leakage again in subsequent drilling construction; third, the existing plugging agents have limited high temperature resistance and cannot effectively plug the pores and cracks in high-temperature formations. In order to solve these problems, it is urgent to develop plugging materials with better performance. Summary of the invention
[0003] The present invention provides a water-based drilling fluid high temperature resistant plugging agent and a preparation method thereof, which overcomes the deficiencies of the above-mentioned prior art and can effectively solve the problem that the existing plugging agents have poor plugging performance under high temperature conditions.
[0004] One of the technical solutions of the present invention is achieved through the following measures: a water-based drilling fluid high temperature resistant plugging agent, the raw materials of which include 10 to 20 parts of embedded particles, 20 to 30 parts of micro-expansion agents, 20 to 30 parts of structural enhancers and 40 to 50 parts of low permeability rigid particles.
[0005] The following is a further optimization and / or improvement of one of the above-mentioned technical solutions: The inlaid particles are formed by mixing polytetrafluoroethylene, zirconium oxide ceramic particles and manganese marble powder in a mass ratio of 1:2:(2.5 to 3.5).
[0006] The particle size of the polytetrafluoroethylene is 100 to 150 meshes, the particle size of the zirconium oxide ceramic particles is 200 to 250 meshes, and the particle size of the manganese marble powder is 300 to 350 meshes.
[0007] The micro-expansion agent is formed by mixing perfluoroether rubber particles and glass fiber reinforced plastic resin particles in a mass ratio of 2: (2.5 to 3.5).
[0008] The particle size of the perfluoroether rubber particles is 300 to 500 meshes, and the particle size of the glass fiber reinforced plastic resin particles is 500 to 1000 meshes.
[0009] The structural reinforcing agent is a mixture of mica flakes and carbon fibers in a mass ratio of 1:(0.5 to 1.5).
[0010] The particle size of the mica flakes is 200 mesh to 300 mesh.
[0011] The low-permeability rigid particles are formed by mixing quartz sand and corundum powder in a mass ratio of 1: (0.5 to 1.5).
[0012] The particle size of the quartz sand is 75 nanometers to 5 micrometers.
[0013] The water-based drilling fluid high temperature resistant plugging agent is obtained by the following method: the required amount of embedded particles, micro-expansion agent, structural reinforcing agent and low-permeability rigid particles are uniformly mixed to obtain the water-based drilling fluid high temperature resistant plugging agent.
[0014] The second technical solution of the present invention is achieved through the following measures: a method for preparing a water-based drilling fluid anti-high temperature plugging agent, which is carried out according to the following method: the required amount of embedded particles, micro-expansion agent, structural enhancer and low-permeability rigid particles are mixed evenly to obtain a water-based drilling fluid anti-high temperature plugging agent.
[0015] The water-based drilling fluid high-temperature resistant plugging agent of the present invention is compounded from various types of materials, has a wide distribution of particle sizes, has stable performance after aging at 180°C, can still form an effective tight seal, and has obvious high-temperature resistance, which effectively overcomes the defects of conventional micro-nano plugging materials that have a single gradation and cannot resist high temperatures. DETAILED DESCRIPTION
[0016] The present invention is not limited by the following embodiments, and specific implementation methods can be determined according to the technical scheme of the present invention and actual conditions. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all known and commonly used chemical reagents and chemicals in the prior art.
[0017] The present invention will be further described below in conjunction with embodiments: Embodiment 1: The water-based drilling fluid anti-high temperature plugging agent comprises raw materials including 10 to 20 parts of embedded particles, 20 to 30 parts of micro-expansion agents, 20 to 30 parts of structural reinforcing agents and 40 to 50 parts of low-permeability rigid particles.
[0018] Embodiment 2: As an optimization of the above embodiment, the inlaid particles are mixed with polytetrafluoroethylene, zirconium oxide ceramic particles and manganese marble powder in a mass ratio of 1:2:(2.5 to 3.5).
[0019] Example 3: As an optimization of the above example, the particle size of polytetrafluoroethylene is 100 mesh to 150 mesh, the particle size of zirconia ceramic particles is 200 mesh to 250 mesh, and the particle size of manganese marble powder is 300 mesh to 350 mesh.
[0020] In the present invention, the raw material mosaic particles are mixed with polytetrafluoroethylene, zirconium oxide ceramic particles and manganese marble powder. The advantages are that the three materials have high hardness, with Mohs hardness above 3.0, and the density of particles with different particle sizes is moderate, which is conducive to suspension and dispersion in drilling fluid. In addition, the reasonable combination of inorganic materials and organic materials makes the mosaic particles have both toughness and rigidity characteristics.
[0021] Embodiment 4: As an optimization of the above embodiment, the micro-expansion agent is formed by mixing perfluoroether rubber particles and fiberglass resin particles in a mass ratio of 2: (2.5 to 3.5).
[0022] Embodiment 5: As an optimization of the above embodiment, the particle size of the perfluoroether rubber particles is 300 mesh to 500 mesh, and the particle size of the fiberglass resin particles is 500 mesh to 1000 mesh.
[0023] In the present invention, the raw material micro-expansion agent is a mixture of perfluoroether rubber particles and glass fiber reinforced plastic resin particles. By utilizing its elastic function, it can deform into the gap under the pressure difference condition, and micro-expand to block the pores after the pressure is released, making the bridge more firm.
[0024] Example 6: As an optimization of the above example, the structural reinforcing agent is a mixture of mica flakes and carbon fibers in a mass ratio of 1: (0.5 to 1.5).
[0025] Example 7: As an optimization of the above example, the particle size of the mica flakes is 200 mesh to 300 mesh.
[0026] In the present invention, the raw material structure reinforcing agent is a mixture of mica flakes and carbon fibers. The combination of flakes and fibers can make the formed plugging have strong toughness and better integrity.
[0027] Example 8: As an optimization of the above example, the low permeability rigid particles are mixed with quartz sand and corundum powder in a mass ratio of 1: (0.5 to 1.5).
[0028] Example 9: As an optimization of the above example, the particle size of the quartz sand is 75 nanometers to 5 micrometers.
[0029] In the present invention, the raw material low permeability rigid particles are formed by mixing quartz sand and corundum powder. Since these two minerals have high hardness, they have good strength retention after crushing. The particle size is a combination of micro and nano grading, which can fill tiny pores. The surface of the nanoparticles is naturally hydrophobic and oleophobic, and the pores can be completely sealed after filling, greatly reducing the blockage permeability.
[0030] Example 10: As an optimization of the above example, the required amount of embedded particles, micro-expansion agent, structural reinforcement agent and low-permeability rigid particles are evenly mixed to obtain a water-based drilling fluid high-temperature resistant plugging agent.
[0031] Example 11: The water-based drilling fluid anti-high temperature plugging agent, the raw materials include 10 parts of inlaid particles (a mixture of polytetrafluoroethylene with a particle size of 100 mesh, zirconia ceramic particles with a particle size of 200 mesh and manganese marble powder with a particle size of 300 mesh in a mass ratio of 1:2:2.5), 20 parts of micro-expansion agent (a mixture of perfluoroether rubber particles with a particle size of 300 mesh and glass fiber reinforced plastic resin particles with a particle size of 500 mesh in a mass ratio of 2:2.5), 20 parts of structural reinforcement agent (a mixture of mica sheets with a particle size of 200 mesh and carbon fiber in a mass ratio of 1:0.5), 40 parts of low-permeability rigid particles (a mixture of quartz sand with a particle size of 75 nanometers and corundum powder in a mass ratio of 1:0.5), which is obtained by the following method: the required amounts of inlaid particles, micro-expansion agent, structural reinforcement agent and low-permeability rigid particles are mixed evenly to obtain the water-based drilling fluid anti-high temperature plugging agent.
[0032] Example 12: The water-based drilling fluid anti-high temperature plugging agent, the raw materials include 10 parts of inlaid particles (a mixture of polytetrafluoroethylene with a particle size of 150 mesh, zirconia ceramic particles with a particle size of 200 mesh and manganese marble powder with a particle size of 300 mesh in a mass ratio of 1:2:3.5), 20 parts of micro-expansion agent (a mixture of perfluoroether rubber particles with a particle size of 500 mesh and glass fiber reinforced plastic resin particles with a particle size of 1000 mesh in a mass ratio of 2:3.5), 20 parts of structural reinforcement agent (a mixture of mica sheets and carbon fibers with a particle size of 300 mesh in a mass ratio of 1:1.5), 40 parts of low-permeability rigid particles (a mixture of quartz sand with a particle size of 5 microns and corundum powder in a mass ratio of 1:1.5), which is obtained by the following method: the required amounts of inlaid particles, micro-expansion agent, structural reinforcement agent and low-permeability rigid particles are evenly mixed to obtain the water-based drilling fluid anti-high temperature plugging agent.
[0033] Example 13: The water-based drilling fluid anti-high temperature plugging agent, the raw materials include 10 parts of inlaid particles (a mixture of polytetrafluoroethylene with a particle size of 150 mesh, zirconia ceramic particles with a particle size of 250 mesh and manganese marble powder with a particle size of 350 mesh in a mass ratio of 1:2:3), 20 parts of micro-expansion agent (a mixture of perfluoroether rubber particles with a particle size of 500 mesh and glass fiber reinforced plastic resin particles with a particle size of 1000 mesh in a mass ratio of 2:3), 20 parts of structural reinforcement agent (a mixture of mica sheets with a particle size of 300 mesh and carbon fiber in a mass ratio of 1:1), 40 parts of low-permeability rigid particles (a mixture of quartz sand with a particle size of 5 microns and corundum powder in a mass ratio of 1:1), which is obtained by the following method: the required amounts of inlaid particles, micro-expansion agent, structural reinforcement agent and low-permeability rigid particles are evenly mixed to obtain the water-based drilling fluid anti-high temperature plugging agent.
[0034] Compared with the prior art, the present invention has the following beneficial effects: The solid phase particles of the present invention are small in size and have a wide range of reasonable particle size distribution, so that the plugging agent can easily enter the leakage channels of various micro-leakage formations. Under the action of pressure difference, it quickly enters the leakage channel. The coarser solid phase particles (micro-expansion agent) and flaky and fibrous materials (structural reinforcing agents) in the water-based drilling fluid anti-high temperature plugging agent of the present invention establish physical support, form a barrier, and establish the initial plugging. The secondary particle size fine particles in the water-based drilling fluid anti-high temperature plugging agent, that is, nano-scale materials (low permeability rigid particles), have strong amphiphilic properties, gradually adhere and fill, and form a denser and firm plugging barrier, which completely blocks the micro-leakage leakage channel. After the blocking barrier is formed, the infiltration of the liquid phase can be greatly reduced. Both oil-based drilling fluid and water-based drilling fluid are applicable and the plugging effect is good.
[0035] The water-based drilling fluid high-temperature resistant plugging agent of the present invention is compounded from various types of materials, has a wide distribution of particle sizes, has stable performance after aging at 180°C, can still form an effective tight seal, and has obvious high-temperature resistance, which effectively overcomes the defects of conventional micro-nano plugging materials that have a single gradation and cannot resist high temperatures.
[0036] Example 14: The water-based drilling fluid anti-high temperature plugging agent, the raw materials include 16g of inlaid particles (mixed with polytetrafluoroethylene with a particle size of 100 mesh, zirconia ceramic particles with a particle size of 200 mesh and manganese marble powder with a particle size of 300 mesh in a mass ratio of 1:2:3), 32g of micro-expansion agent (mixed with perfluoroether rubber particles with a particle size of 300 mesh and glass fiber reinforced plastic resin particles with a particle size of 500 mesh in a mass ratio of 2:3), 48g of structural reinforcing agent (mixed with mica sheets and carbon fibers with a particle size of 200 mesh in a mass ratio of 1:1), 64g of low-permeability rigid particles (mixed with quartz sand and corundum powder with a particle size of 75 nanometers in a mass ratio of 1:1), which is obtained by the following method: the required amounts of inlaid particles, micro-expansion agent, structural reinforcing agent and low-permeability rigid particles are mixed evenly to obtain the water-based drilling fluid anti-high temperature plugging agent.
[0037] Example 15: The difference from Example 14 of the present invention is that the raw materials include 24g of mosaic particles, 40g of micro-expander, 48g of structural enhancer and 48g of low-permeability rigid particles, and the selection and preparation methods of the remaining raw materials are the same.
[0038] Example 16: The difference from Example 14 of the present invention is that the raw materials include 32g of mosaic particles, 32g of micro-expander, 48g of structural enhancer and 48g of low-permeability rigid particles, and the selection and preparation methods of the remaining raw materials are the same.
[0039] Example 17: The difference from Example 14 of the present invention is that the raw materials include 16g of mosaic particles, 48g of micro-expander, 48g of structural enhancer and 48g of low-permeability rigid particles, and the selection and preparation methods of the remaining raw materials are the same.
[0040] Comparative Example 1: Existing known plugging agent while drilling.
[0041] Comparative Example 2: Existing well-known ultrafine calcium plugging agent.
[0042] Example 18: The performance of the water-based drilling fluid anti-high temperature plugging agent of the present invention was tested. The water-based drilling fluid anti-high temperature plugging agent prepared in Examples 14 to 17 of the present invention was mixed with clean water to form a plugging slurry. After high-temperature aging at 180°C for 16 hours, the plugging effect of each plugging slurry on a 40-80 mesh sand bed was tested. At the same time, the existing drilling plugging agent and ultrafine calcium plugging agent were used for comparison.
[0043] Specific preparation method of plugging slurry: (1) Measure 6 cups of 400 ml clean water and place them on a high-speed stirrer; take 16 g of the water-based drilling fluid high-temperature anti-plugging agent prepared in Examples 14 to 17 and Comparative Examples 1 to 2 respectively and set aside.
[0044] (2) Turn on the stirrer at 11000 rpm and add the plugging agent into the clean water. Stir for 20 minutes. During this time, use a glass rod to scrape off the adhesion on the wall of the cup.
[0045] (3) Transfer each plugging slurry into a curing tank, place it in a roller heating furnace and roll it at 180°C for 16 hours. After cooling and depressurizing, pour out the plugging slurry and place it on a high-speed agitator.
[0046] (4) After starting the agitator and stirring at 11,000 rpm for 2 min, 1.6 g of xanthan gum was added and stirred again at 11,000 rpm for 20 min. During this time, the adherent material adhering to the cup wall was scraped off with a glass rod to obtain a plugging slurry.
[0047] The prepared plugging slurry is subjected to a sand bed pressure bearing capacity test.
[0048] Specific test method: Use GGS71-A high-temperature and high-pressure filtration meter, do not add filter paper (filter surface) to the drilling fluid cup, add 300g of 40-80 mesh quartz sand, and when the lower ventilation valve stem is open, use a small iron rod to insert the quartz sand tightly, compact and flatten it, and use a glass rod to drain the sample slurry and slowly add 400ml to the high-temperature and high-pressure drilling fluid cup; install the upper cover of the high-temperature and high-pressure drilling fluid cup and lock it, place a measuring cylinder at the lower ventilation valve to collect the filtrate, open the upper valve stem and slowly pressurize to 0.7MPa, stabilize the pressure for 10min, then slowly and evenly pressurize to 5.0MPa, stabilize the pressure for 30min, and the filtration loss is less than 30mL, the experiment is successful.
[0049] Test results: The pressure bearing capacity results are shown in Table 1. It can be seen from Table 1 that when the comparative example 1 of the present invention was pressurized to 0.7 MPa, all leakage occurred, and gas came out of the bottom outlet. When the comparative example 2 of the present invention was pressurized to 2 MPa, all leakage occurred, and gas came out of the bottom outlet. However, the water-based drilling fluid anti-high temperature plugging agents prepared in Examples 14 to 17 of the present invention had no filtration loss after being pressurized to 5 MPa and stabilizing the pressure for 30 minutes, indicating that the water-based drilling fluid anti-high temperature plugging agent of the present invention effectively plugged the sand bed. The plugging performance of the high temperature plugging agent for water-based drilling fluid of the present invention is significantly better than that of the plugging agent while drilling and the ultrafine calcium plugging agent, and a good plugging effect is exerted.
[0050] In summary, the water-based drilling fluid high-temperature resistant plugging agent of the present invention is compounded from various types of materials, has a wide particle size distribution, and has stable performance after aging at 180°C. It can still form an effective tight seal and has obvious high-temperature resistance. It effectively overcomes the defects of conventional micro-nano plugging materials with a single gradation and inability to resist high temperatures.
[0051] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.
Claims
1. A water-based drilling fluid high temperature resistant plugging agent, characterized in that The raw materials include 10 to 20 parts of inlaid particles, 20 to 30 parts of micro-expanding agents, 20 to 30 parts of structural reinforcing agents and 40 to 50 parts of low-permeability rigid particles.
2. The water-based drilling fluid high temperature resistant plugging agent according to claim 1, characterized in that The inlay particles are mixed with polytetrafluoroethylene, zirconium oxide ceramic particles and manganese marble powder in a mass ratio of 1:2:2.5 to 3.
5.
3. The water-based drilling fluid high temperature resistant plugging agent according to claim 2, characterized in that The particle size of polytetrafluoroethylene is 100 mesh to 150 mesh, the particle size of zirconia ceramic particles is 200 mesh to 250 mesh, and the particle size of manganese marble powder is 300 mesh to 350 mesh.
4. The water-based drilling fluid high temperature resistant plugging agent according to any one of claims 1 to 3, characterized in that The micro-expansion agent is prepared by mixing perfluoroether rubber particles and glass fiber reinforced plastic resin particles in a mass ratio of 2:2.5 to 3.
5.
5. The water-based drilling fluid high temperature resistant plugging agent according to claim 4, characterized in that The particle size of the perfluoroether rubber particles is 300 meshes to 500 meshes, and the particle size of the glass fiber reinforced plastic resin particles is 500 meshes to 1000 meshes.
6. The water-based drilling fluid high temperature resistant plugging agent according to any one of claims 1 to 5, characterized in that The structural reinforcement is a mixture of mica flakes and carbon fibers in a mass ratio of 1:0.5 to 1.
5.
7. The water-based drilling fluid high temperature resistant plugging agent according to claim 6, characterized in that The particle size of the mica flakes is 200 mesh to 300 mesh.
8. The water-based drilling fluid high temperature resistant plugging agent according to any one of claims 1 to 7, characterized in that The low-permeability rigid particles are prepared by mixing quartz sand and corundum powder in a mass ratio of 1:0.5 to 1.5, and the particle size of the quartz sand is 75 nanometers to 5 microns.
9. The water-based drilling fluid high temperature resistant plugging agent according to any one of claims 1 to 8, characterized in that The method is as follows: the required amount of embedded particles, micro-expansion agent, structural reinforcing agent and low-permeability rigid particles are uniformly mixed to obtain a water-based drilling fluid high-temperature resistant plugging agent.
10. A method for preparing the water-based drilling fluid high temperature resistant plugging agent according to any one of claims 1 to 8, characterized in that The method is as follows: the required amount of embedded particles, micro-expansion agent, structural reinforcing agent and low-permeability rigid particles are uniformly mixed to obtain a water-based drilling fluid high-temperature resistant plugging agent.